Answer:
a line parallel to the line y = 5x + 2 ---> y' = 5x + b (b ≠ 2)
y' = 5x + b goes through (-4, 3) ---> 3 = 5 × ( -4 ) + b ---> b = 23
⇒ y' = 5x + 23
Answer:
g + 5h - 2j - 10
Step-by-step explanation:
-3g + 5h -2j - 5 + 4g - 5
simplify using like terms
-3g + 4g = 1g or "g"
5h
-2j
-5 + (-5) = -10
g + 5h - 2j - 10
5h and -2j didn't have any like terms.
The correct answer is $35
The correct answer is C. if you plug zero in for 'x' you will get the y-intercept.
-2(0-2)(0-4)= -2(-2)(-4)=-16
Next set each factor equal to zero to get the x-intercepts.
(x-2)=0 x = 2 (2,0)
(x-4) = 0 x = 4 (4,0)
I hope this helps
Answer:
The answer is 15/52. (Please make me as brainliest (: )